Effect of oceanographic conditions on skipjack tuna catches from FAD versus free-swimming school fishing in the Makassar Strait. (November 2019) - Putri, A R S; Zainuddin, M; Musbir, M; Mustapha, M A; Hidayat, R
Abstract: Fish Aggregating Devices (FADs) have become the preferred choice in skipjack tuna fisheries rather than looking for free-swimming schools (FSS) which is considered less effective. This study aimed to identify the effect of oceanographic conditions on skipjack tuna catches in the FADs versus free-swimming schools in the Makassar Strait. We collected fishing data from vessels using purse seine fishing gear and satellite-based oceanographic data (Sea Surface Temperature (SST) and chlorophyll-a (chl-a)) from May to July 2017. The satellite and catch data were analysed using a Generalized Additive Model implemented in R and mapped using Spatial Analyst in ArcGIS 10.6. The results showed that SST ranges in the FAD areas were relatively wider (29 – 31°C) than those in free-swimming school areas (29.5 – 30.5°C). The chl-a concentrations in free-swimming school areas were relatively higher (0.25 – 0.80 mg m-3) than those in the FAD areas (0.15 – 0.50 mg m-3). It was also found that mean skipjack tuna catches in the FAD areas (337 fish/setting) were relatively higher than in the free-swimming school areas (145 fish/setting). These findings suggest that the high skipjack tuna catches in Makassar Strait were significantly affected by specific SST ranges and relatively low chl-a.